2002
DOI: 10.1038/sj.bjp.0704493
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide prevents oxygen radical production by human neutrophils: possible mechanism(s) involved in its anti‐inflammatory effect

Abstract: 1 We have reported that andrographolide (ANDRO), an active component of Andrographis paniculata, inhibits in¯ammatory responses by rat neutrophils. To further elucidate the possible mechanism(s) underlying the ANDRO's e ect, N-formyl-methionyl-leucyl-phenylalanine (fMLP)-induced adhesion and transmigration of isolated peripheral human neutrophils were studied. 2 Pretreatment with ANDRO (0.1 ± 10 mM) concentration-dependently prevented fMLP-induced neutrophil adhesion and transmigration. We further examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
177
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(183 citation statements)
references
References 35 publications
6
177
0
Order By: Relevance
“…It was found that andrographolide had wide bioactivities, such as anti-inflammatory antibiotic (Sinha et al, 2000;Shen et al, 2002), anti-platelet aggregation (Zhang and Tan, 1997;Amroyan et al, 1999), and anti-human immunodeficiency virus activities (Calabrese et al, 2000). Andrographolide was widely used in the clinic, but it was not effective in vitro.…”
mentioning
confidence: 99%
“…It was found that andrographolide had wide bioactivities, such as anti-inflammatory antibiotic (Sinha et al, 2000;Shen et al, 2002), anti-platelet aggregation (Zhang and Tan, 1997;Amroyan et al, 1999), and anti-human immunodeficiency virus activities (Calabrese et al, 2000). Andrographolide was widely used in the clinic, but it was not effective in vitro.…”
mentioning
confidence: 99%
“…It possesses antimicrobial (Prajjal et al, 2003), anti-inflammatory (Shen et al, 2002), hypotensive ( Zhang and Tan, 1996) , antihyperglycemic ( Yu et al, 2003;Borhanuddin et al ., 1994); oxygen radical scanvenging (Shen et al, 2002), atherosclerotic ( Wang and Zhao.,1994), anti-malarial activity (Dua et al,2000), anti-HIV (Calabrese et al,2000), antiplatelet aggregation (Amroyan et al,1999), hepatic lipid peroxidation protective (Choudhury and Poddar,1984), hepatoprotective (Handa and Sarma ,1990), choleretic effect (Shukla et al, 1992), and anticancer effects (Kumar et al,2004 ;Rajagopal et al 2003;Chang, 1987;Matsuda et al, 1994 ). One of the major constituents of A. paniculata Ness is diterpene lactone such as andrographolide, which has anticancer activity in vitro in many tumor cell lines including leukemia, myeloma, HeLa, colon (HT-29), human peripheral blood lymphocytes (HPBLs), and human breast cancer MCF-7 (Satyanaraya et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…5) In Thailand, this plant was selected by the Ministry of Public Health as one of the medicinal plants to be included in "The National List of Essential Drugs A.D. 1999" (List of Herbal Medicinal Products). 6) Extensive research has revealed that Andrographis paniculata has a surprisingly broad range of pharmacological effects and some of them are extremely beneficial, such as antiinflammatory, [7][8][9][10][11] antidiarrhoeal, 12,13) antiviral, 14) anti-malarial, 15,16) hepatoprotective, [17][18][19][20][21][22][23][24][25][26][27][28][29] cardiovascular, 30,31) anticancer, [32][33][34][35][36][37][38][39] and immunostimulatory [40][41][42][43][44] activities. On the other hand, male reproductive toxicity 45) and cytotoxicity 46) of this plant have been reported as well.…”
Section: Introductionmentioning
confidence: 99%